FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Setianingsih Setianingsih; Yulianto Yulianto (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to examine the factors influencing voluntary disclosure in the annual reports of companies listed on the Jakarta Islamic Index. The variables studied are profitability, liquidity, and company size. Previous research on voluntary disclosure has been conducted, but the results have been varied and inconsistent. The research method used is quantitative with panel data regression analysis. The data used consists of annual financial reports of companies from the period 2012-2021 obtained from the official website www.idx.co.id and company websites. The results of the study indicate that the variables profitability and liquidity, partially, do not have a significant effect on voluntary disclosure, while company size, partially, has a significant effect on voluntary disclosure. Simultaneous testing results show that profitability, liquidity, and company size have a significant effect on voluntary disclosure.